TINJAUAN HUKUM PIDANA ISLAM TERHADAP PELAKU PENYERTAAN TINDAKPIDANA ABORSI DALAM PUTUSAN NOMOR PERKARA 1106/PID.SUS/2018/PN.PLG - mega aini; M Tamudin; Jumanah Jumanah (Universitas Islam Negeri Raden Fatah Palembang, 2021)
Based on the division ofcrime ta'zir above, helping to perform abortion is included in the first category ofcrime ta'zir , namely the criminal act of hudud or qisas which is confirmed by the Koran and hadith, but the conditions are not fulfilled by syubhat. The defendant in this case did not have a complete abortion, it was just that the defendant had already given an injection and also gave medicine to drink so that the fetus in the womb could fall. The data source used is secondary data which consists of three parts, namely, primary legal materials, secondary legal materials and tertiary legal materials. Primary legal materials are binding legal materials in the form of Al-Qur'an and Hadith, the 1945 Constitution, and applicable regulations. The results of the research show that the perpetrator of a criminal act helped to carry out an abortion in decision number 1106 / Pid.sus / 2018 / PN.Plg. sentenced to imprisonment for 4 (four) years and revoked license to practice, because it has been proven to have committed a criminal act of assisting attempted abortion in accordance with the facts in the trial, the testimony of witnesses, the testimony of the defendant, taking into account the evidence presented and examined at trial, factors relating to matters that incriminate and relieve the defendant. And analysis of Islamic criminal law against abortion cases help conduct experiments included in the category jarimah ta'zir derived from jarimah hudud or qishas, but its conditions are not met by doubtful. So the imposition of the punishment is left to the government / state authorities (ulil amri). Keywords: Inclusion, Abortion, Decision